Respuesta :

Use the distance formula to find the distance between two points.
For any points [tex]P(x_1,\ y_1)[/tex] and [tex]Q(x_2,\ y_2)[/tex], the distance between them [tex]PQ=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]

[tex]EA=\sqrt{(3-5)^2+(1-1)^2}=\sqrt{(-2)^2+0^2}=\sqrt{4}=2[/tex]
[tex]EB=\sqrt{(3-2)^2+(1-4)^2}=\sqrt{1^2+(-3)^2}=\sqrt{1+9}=\sqrt{10}[/tex]
[tex]EC=\sqrt{(3-3)^2+(1-7)^2}=\sqrt{0^2+(-6)^2}=\sqrt{36}=6[/tex]
[tex]ED=\sqrt{(3-7)^2+(1-2)^2}=\sqrt{(-4)^2+(-1)^2}=\sqrt{16+1}=\sqrt{17}[/tex]

The correct answer is C(3, 7).
(you don't even need to use the distance formula to realize this since it's 6 units directly above E(3, 1))